Mapping Digital Technology Adoption for Sustainable Development: A Bibliometric Analysis - Kerkulah P Nyeleker; Achmad Nurmandi; Herman Lawelai; Muhammad Younus; Wahdania Suardi (INJECT (Interdisciplinary Journal of Communication), 2026)
This study employs a qualitative bibliometric approach to map research on digital technology adoption for sustainable development. Data were drawn from Scopus-indexed publications published between 2015 and 2025. The PRISMA flowchart was used to document the screening process, while VOSviewer and RStudio–Biblioshiny supported the analysis of publication trends, thematic structures, and research evolution. The findings show that scholarly output in this field was limited before 2020 but increased sharply thereafter, reflecting growing interest in sustainability-oriented digital transformation. Frequently occurring keywords such as sustainable development, digital transformation, sustainability, and digital technologies indicate a strong integration of policy and governance perspectives. Thematic analyses further reveal increasing attention to behavioural and institutional factors, with technology acceptance frameworks, particularly the Unified Theory of Acceptance and Use of Technology (UTAUT), emerging as an important but still underexplored research stream. Based on these mapped patterns, the study outlines a conceptually informed extension of UTAUT to highlight key sustainability-related adoption drivers identified in the literature. The framework is presented as an agenda-setting outcome of the bibliometric synthesis, intended to support future empirical research rather than to offer a validated theoretical model.